Internal Force Calculation Method for Beams and Columns Based on Solid Numerical Calculation Results - WEI Gang; YU Jun; LEI Yong; WU Jianxing; SHI Chong; QIU Liewang (Renmin Zhujiang)
Solid elements are commonly used for continuous numerical simulations such as finite element and finite difference.The calculation results typically include stress,deformation,and plastic zones.However,these results cannot be directly used for reinforcement design of engineering structures,which are usually reinforced based on internal forces such as bending moment,axial force,and shear force.To address this,we propose a method to calculate the stress of each cross-section point using the linear interpolation method of element edges.The cross-section mesh is divided evenly based on the number of cross-section points,and the divided mesh is considered as the action area of the cross-section point stress to calculate the internal force.Additionally,we calculate the internal force values,including axial force,shear force,and bending moment,for the entire section.We utilize AutoCAD as the result display platform to develop a program that converts the calculation results of solid stress into an internal force diagram.We validate the program using a simple model and apply it to the reinforcement design of specific engineering beams and columns.The research results can serve as a reference for reinforcement analysis based on solid element numerical calculations.